The effectiveness of HRIS by using Technology Acceptance Model (TAM) on human resources performance at Majlis Perbandaran Kluang (MPK) / Nur Amalina Rahman - Rahman, Nur Amalina (Faculty of Business and Management, 2013)
This study was conducted to explain the effectiveness of Human Resources Information System (HRIS) on Human Resources Performances. The subject area for this study is Majlis Perbandaran Kluang (MPK), lohor and in measuring the effectiveness of using HRIS to perform their organizational performance the researcher decided to use Technology Acceptance Model (TAM) created by Davis (1989) to measure the acceptance of employees at MPK towards HRIS. This study involves 164 (s=l13) respondents with three different levels of employee which are top, middle and lower management. A pilot survey study was carried out to identify the problem of using questionnaire with 30 respondents from each level of management at MPK. The 164 structural questionnaire then has been used to collect data from the respondents and the answer received from 121 respondents were analyzed but only 85 respondents complete answer the questionnaire. This research study also focuses more on how the organization identifies and fully utilize the functionality of information system for example HRIS and how the effectiveness of HRIS have a relationship with employee acceptance. The level of measurement of effectiveness will include the Human Resources process, information effects, time and cost savings, and decision making process. Besides that, a set of questionnaire will be distributed to respondents and the information will be collected as part of the sources of data for this research study. The keywords for this study are Information System, Human Resources Information System (HRIS), Technology Acceptance Model (TAM), Perceived Ease of Use, Perceived Usefulness,Perfonnance and Human Resources. The results indicate from the findings shows that all of these elements have significant positive relationships and it answered research questions as well as support the hypotheses presented in this research study. As a conclusion, this research study helps the other researcher to explore the effectiveness of HRIS in the human resource perfonnance. This research study result supported by previous results that presented at every research findings .